Produksi Kitosan dari Cangkang Rajungan (Portunus sp.) pada Suhu Ruang: The Production of Chitosan from Crab Shell (Portunus sp.) at Room Temperature - Dessy Atika Natalia; Niken Dharmayanti; Fera Roswita Dewi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Crab shell (Portunus Sp) can be used as a raw material for chitosan which obtained by hydrolyzing chitin by using strong alkali and high temperature. The use of high temperature during the process, producing chitosan without any thermal stage can be a possible solution to reduce hazard. The study aims to produce chitosan from crab shells using non thermal method. Chitosan was made through these stages: deproteination, demineralization and deacetylation. The yielded chitosan then characterized. The results showed that the chitosan has yellowish white color, in flakes form and odorless with moisture content 11,25 – 12,93%, ash content 1,62 – 1,75%, nitrogen content 5,12 – 5,45%, lipid content 0,25 – 0,49%, viscosity 37,50 – 38,33 cPs, solubility 99,55 – 99,57% and degree of deacetylation 57,64%. In conclusion chitosan can be made with non thermal method met the commercial standards of chitosan except for the low deacetylation. Processing chitosan with non thermal methode can be applied at small crab miniplant, thus the crab shells has more economical value.